Knowledge as a Way Home: Philosophy of Unity of Sciences in Responding the Crisis of Meaning in Modern Education - Fitriana Wijaya (Karakter : Jurnal Riset Ilmu Pendidikan Islam, 2026)
Knowledge should not only make human beings intellectually capable, but also guide them to understand the meaning and direction of life. However, in modern education, knowledge is often reduced to an instrument for obtaining grades, degrees, employment, and material success. This condition indicates a crisis of meaning in education, where knowledge grows rapidly but is not always followed by moral awareness and spiritual maturity. This article examines the Philosophy of Unity of Sciences as an alternative paradigm to restore the meaning of knowledge in modern education. This study uses library research with a descriptive-critical approach. The primary sources include the Qur’an, Hadith, Al-Ghazali’s Iḥyā’ ‘Ulūm Al-Dīn, Syed Muhammad Naquib Al-Attas’ Islam and Secularism, and the Javanese ethical text Serat Wedhatama. This article is also strengthened by the thoughts of Muslim scholars such as Al-Kindi, Al-Farabi, Ibn Sina, Al-Biruni, Ibn Al-Haytham, Al-Khawarizmi, and Ibn Khaldun. The result of this study shows that the Philosophy of Unity of Sciences views all knowledge as originating from Allah. Therefore, religious knowledge and general knowledge should not be separated or opposed to each other. Both should work together to form human beings who are faithful, rational, ethical, and responsible. In this sense, knowledge can be understood as “a way home”, namely a way to return to God, to the self, to humanity, and to nature.